2012
DOI: 10.1186/1471-2164-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in parasitic nematode genomes: the microRNAs of Brugia pahangi and Haemonchus contortus are largely novel

Abstract: BackgroundMicroRNAs (miRNAs) play key roles in regulating post-transcriptional gene expression and are essential for development in the free-living nematode Caenorhabditis elegans and in higher organisms. Whether microRNAs are involved in regulating developmental programs of parasitic nematodes is currently unknown. Here we describe the the miRNA repertoire of two important parasitic nematodes as an essential first step in addressing this question.ResultsThe small RNAs from larval and adult stages of two paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
134
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(138 citation statements)
references
References 75 publications
4
134
0
Order By: Relevance
“…A recent review includes the information on the specific sequences found in parasites and their homologies with miRNA sequences of other organisms [2]. After this review, the number of identified miRNA sequences in parasites in which miRNAs were already known has increased due to large scale sequencing experiments, and new miRNA sequences have been also described in parasites in which miRNAs had not been evidenced before (see http://www.mirbase.org/search.shtml; [12][13][14][15]; Fig. 1).…”
Section: Micrornas In Parasites: a Growing Collection Of Sequence Infmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review includes the information on the specific sequences found in parasites and their homologies with miRNA sequences of other organisms [2]. After this review, the number of identified miRNA sequences in parasites in which miRNAs were already known has increased due to large scale sequencing experiments, and new miRNA sequences have been also described in parasites in which miRNAs had not been evidenced before (see http://www.mirbase.org/search.shtml; [12][13][14][15]; Fig. 1).…”
Section: Micrornas In Parasites: a Growing Collection Of Sequence Infmentioning
confidence: 99%
“…In the last five years, parasite nematodes have also been candidates of miRNA studies, e.g. Trichinella spiralis and Haemonchus contortus [24,25,15]. These studies have shown interesting relationships between changes in the miRNA microenvironment linked to specific parasite life-cycle stages, and between the promotion of drug resistance and the presence of defined miRNAs, among others.…”
Section: Micrornas In Parasites: a Growing Collection Of Sequence Infmentioning
confidence: 99%
“…Recent deep sequencing projects have revealed the presence of many miRNA homologues in nematode parasites (reviewed in (Britton et al, 2014)). These include Ascaris suum (Wang et al, 2011), Brugia pahangi (Winter et al, 2012), Dirofilaria immitis (Fu et al, 2013) and the human filarial parasite Brugia malayi (Poole et al, 2010, 2014). While some putative miRNAs in parasitic nematodes are highly conserved, a large proportion appear to be novel (Winter et al, 2012).…”
mentioning
confidence: 99%
“…These include Ascaris suum (Wang et al, 2011), Brugia pahangi (Winter et al, 2012), Dirofilaria immitis (Fu et al, 2013) and the human filarial parasite Brugia malayi (Poole et al, 2010, 2014). While some putative miRNAs in parasitic nematodes are highly conserved, a large proportion appear to be novel (Winter et al, 2012). Furthermore, many of the putative parasitic nematode miRNAs are restricted to certain lifecycle stages, suggesting that they function in developmental control of gene expression (Winter et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation